Labour orators from Bevan to Miliband - Hayton, Richard; Crines, Andrew Scott (Book collections on Project MUSE., 2015)
How do leading Labour figures strive to communicate with and influence the electorate? Why have some proven more successful than others in advancing their ideological arguments? How do orators seek to connect with different audiences in different settings such as parliament, party conference and through the media? This collection evaluates these questions as well as providing an extensive interrogation of the political and intellectual significance of oratory and rhetoric in the post-war Labour Party.